Intercellular adhesion molecule-1 (ICAM-1) deficiency protects mice against severe forms of experimentally induced colitis - Bendjelloul, F; Malý, P; Mandys, V; Jirkovská, M; Prokesová, L; Tucková, L; Tlaskalová-Hogenová, H (Clinical and experimental immunology, 2000)
ICAM-1 (CD54), the ligand for LFA-1 and Mac-1, is up-regulated during inflammatory reaction on the activated vascular endothelium. To determine its role in intestinal inflammation, we induced acute experimental colitis in mice with a deleted ICAM-1 gene, by feeding them with 3% dextran sodium sulphate (DSS) in drinking water for 7 days. Chronic colitis was elicited by DSS similarly, followed by 2 weeks with water. In the acute phase of inflammation, ICAM-1-deficient mice exhibited a significantly lower mortality rate (5%) than control C57Bl/6J mice (35%). Control animals, but not the ICAM-1-deficient mice, exhibited diarrhoea and rectal bleeding. Histological examination of large-bowel samples evaluated the intensity of inflammatory changes, and type and extent of mucosal lesions. In the acute phase, 33.3% of samples from ICAM-1-deficient mice exhibited mucosal defects (flat and fissural ulcers), predominantly mild to moderate inflammatory infiltrate within the lamina propria mucosae and lower grades of mucosal lesions. Much stronger inflammatory changes were present in control animals, flat ulcers (sometimes multiple) and fissural ulcers being observed in 62.5% of samples. Mucosal inflammatory infiltrate was moderate to severe, typically with higher grades of mucosal lesions. In chronic colitis, smaller inflammatory changes were found in the large bowel. The two mouse strains differed, the chronic colitis being accompanied by an increased serum level of anti-epithelial IgA autoantibodies in C57Bl/6 control mice but not in ICAM-1-deficient mice. These findings provide direct evidence of the participation of ICAM-1 molecule in the development of experimentally induced intestinal inflammation.
Keywords: Autoantibodies; Dextran Sulfate; Female; zvířata; Immunoglobulin A; myši; myši inbrední C57BL; Mice; myši knockoutované; síran dextranu; ženské pohlaví; mezibuněčná adhezivní molekula-1; Mice, Knockout; autoprotilátky; Mice, Inbred C57BL; imunoglobulin A; kolitida; Animals; Intercellular Adhesion Molecule-1; Disease Models, Animal; Colitis; modely nemocí na zvířatech